TECHNOLOGY OF INCULCATING NATIONAL SPIRITUAL VALUES IN PRIMARY SCHOOL STUDENTS IN MOTHER TONGUE AND READING LITERACY CLASSES (Academia Science Repository, 2023)
The article focused on the possibilities of interactive methods, information and telecommunication tools, which are intended to be used in teaching the technology of instilling national-spiritual values to primary school students in the education and mother tongue and reading literacy classes.